2022
DOI: 10.1007/s12325-022-02338-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns and Treatment Satisfaction Among Adults with Alopecia Areata in the United States

Abstract: Introduction: Alopecia areata (AA), an autoimmune disease, is characterized by non-scarring hair loss involving the scalp, face, and/or body. Prior to 2022, no US Food and Drug Administration (FDA)-approved treatments for AA were available in the USA; existing treatment options had limited efficacy and durability and are often associated with side effects. This study aimed to evaluate the current AA treatment patterns and treatment satisfaction as reported by dermatologists. Methods: Real-world data from a 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…Use of conventional immunosuppressants increased with disease severity and subsequent lines of therapy. Similar patterns have been observed in the United States [29]. This is consistent with published expert opinions that position conventional immunosuppressants mostly for adult patients with severe AA and generally after corticosteroids or as steroid-sparing agents [18,26,27].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Use of conventional immunosuppressants increased with disease severity and subsequent lines of therapy. Similar patterns have been observed in the United States [29]. This is consistent with published expert opinions that position conventional immunosuppressants mostly for adult patients with severe AA and generally after corticosteroids or as steroid-sparing agents [18,26,27].…”
Section: Discussionsupporting
confidence: 87%
“…In a recent study in Japan, topical corticosteroids were the most frequently prescribed treatment for AA [28]. Several studies have described treatment patterns in the United States and reported similar findings [29][30][31]. Despite limited evidence, corticosteroids remain the mainstay of AA pharmacological management [7,26].…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 7 , 8 Overall, patients and dermatologists considered their experience with commonly used traditional therapies to be unsatisfactory. 3 , 7 , 9 There have therefore been numerous calls for more effective treatment options. 2 , 10 , 11 With a greater understanding of disease pathogenesis, the development of new treatments for AA have been successful and approved.…”
Section: Introductionmentioning
confidence: 99%